Macho dancer - Lee, Ricardo; Lacuesta, Amado; Brocka, Lino; Tutanes, Joe; De Guia, Boy C. (Viva platinum, 2005)
Abandoned by his American lover, a handsome teenager from the mountains journeys to Manila in an effort to support his family. With a popular call boy as his mentor, Paul enters the glittering world of the "macho dancer"--A world of male strippers, prostitution, drugs, sexual slavery, police corruption and murder.